The Impact Of People's Business Credit Financing On Improving The Financial Performance Of UMKM Assisted By Bank Syariah Indonesia Tanjung Branch Office, South Kalimantan - Dwi Jayanti Ratna Kumala Sari; Faqih El Wafa; Badrian; Pati Matu Jahra (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2024)
This research is motivated by the problem of limited business capital in Micro, Small and Medium Enterprises (MSMEs) so that they have not been able to develop their business. For this reason, this study aims to determine and understand the impact of People's Business Credit (KUR) financing on the performance of Micro, Small and Medium Enterprises in Tabalong Regency and the People's Business Credit distribution system implemented by the Bank Syariah Indonesia (BSI) Tanjung Branch Office. the research used is field research with a qualitative approach method. Data were collected using interviews and documentation. The data extracted through interviews is data regarding the people's business credit distribution system, as well as information regarding assets, turnover and net income of MSME actors. In addition, documentation is needed to track and strengthen data on changes in MSME performance in terms of assets, turnover and net profit from before getting and after getting People's Business Credit and coaching from Bank Syariah Indonesia KC Tanjung. The subjects in this study were 13 informants, including 10 MSMEs and 3 Micro Employees of Bank Syariah Indonesia (BSI) Tanjung Branch Office. The analysis technique used the Miles and Huberman model by carrying out data collection, data reduction, data presentation and conclusion drawing The results of the study prove that KUR financing on the performance of MSMEs has a positive impact. This can be proven by the impact on the level of assets, turnover and net profit which has increased by up to 40%. So KUR financing is very helpful for MSMEs in increasing business capital so that the resulting performance has good quality from increased income. This research not only proves qualitatively that People's Business Credit can have a positive impact on the performance of MSMEs, but also provides other alternatives for the government and other financial institutions in channeling capital assistance to MSMEs, namely with the Assisted MSME model.